Thrifty science making the most of materials in the history of experiment - Werrett, Simon (The University of Chicago Press, 2019)
If the twentieth century saw the rise of "Big Science," then the seventeenth and eighteenth centuries were surely an age of thrift. As Simon Werrett's new history shows, frugal early modern experimenters transformed their homes into laboratories as they recycled, repurposed, repaired, and reused their material possessions to learn about the natural world. 0Thrifty Science explores this distinctive culture of experiment and demonstrates how the values of the household helped to shape an array of experimental inquiries, ranging from esoteric investigations of glowworms and sour beer to famous experiments such as Benjamin Franklin's use of a kite to show lightning was electrical and Isaac Newton's investigations of color using prisms. Tracing the diverse ways that men and women put their material possessions into the service of experiment, Werrett offers a history of practices of recycling and repurposing that are often assumed to be more recent in origin. This thriving domestic culture of inquiry was eclipsed by new forms of experimental culture in the nineteenth century, however, culminating in the resource-hungry science of the twentieth. Could thrifty science be making a comeback today, as scientists grapple with the need to make their research more environmentally sustainable?